Improvement of assessment practices in secondary schools in Nigeria (2011)
"Continuous Assessment (CA) Practice in the secondary schools in Nigeria is wrongly practised while the Assessment For Learning (AFL) which should be a complementary aspect of CA is not well known or practised. The main objectives of this paper are: (i) to intimate the stakeholders in education with the level of awareness of CA and AFL in secondary schools in Nigeria, (ii) to enlighten the classroom teachers on the effective way of practising CA and AFL, (iii) to enlighten the learners on self-assessment through the remarks of teachers on their performances in various tests, and (iv) to encourage and prepare learners and teachers on effective implementation of CA and AFL. The end product of this exercise is to enhance effective assessment which will eventually lead to improvement in the learning process, The paper looked into the antecedent of CA and AFL in the secondary schools, as well the current level of practice of the two approaches in some states of the federation. The paper emphasized the fact that CA practice is guidance- oriented and formative in nature while AFL encourages the learners to have individual assessment of themselves hence the two approaches are learner centred. The writer made use of research findings af other academics as well as her own wealth of experience as classroom teccber and principal of a school in he: fast 25 years in the secondary schools in Oyo state of Nigeria. Lastly, recommendations were made for federal and state governments on capacity building for teachers and quality control personnel so that capacity building for teachers and quality control personnel so that teaching and asessment could be and state governments on capacity building for teachers and quality control personnel so that teaching and assessment could be effective in the Nigerian secondary schools."